The natural farming model of Andhra Pradesh: a solution for sustainable agriculture in India - Gupta, Shweta; Malaiappan, Sudharsan; Krishnan, S.; Sikka, Alok (International Water Management Institute, 2023)
Andhra Pradesh, also known as the `rice bowl of India’, is one of the largest states in the country, where more than 60% of the population depends on agriculture for their livelihood. The state is divided into six agro-climatic zones making it conducive to growing a wide range of crops throughout the year such as rice, cotton, groundnuts, pulses, oilseeds, and coarse grains. It has been one of the front-runners in reaping the benefits of the green revolution (1960s) and the first state in India to create the necessary infrastructure to facilitate direct benefit transfer of subsidies in agriculture including fertilizers, power supply, credit, irrigation, and farm machinery, among others. However, several technological, environmental and policy- related challenges exist such as huge dependence on monsoons, overutilization of chemical inputs affecting soil health, liberal power and irrigation subsidies (See below note #1) causing overexploitation of groundwater and limited public sector investment limiting agriculture growth in the state. Taking note of the need for sustainable agriculture, the state government of AP launched Zero Budget Natural Farming in 2016 as an alternative to chemical-based and capital-intensive agriculture, through its implementing agency Rythu Sadhikara Samstha (RySS). This scheme was later renamed as Andhra Pradesh Community Managed Natural Farming (APCNF).